Educational Method in the Quran: Analysis of Islamic Education Science Surah An-Nahl Verse 125 - Muhammad Syauqi Mubarok; Reski Ramadhani; Marissa Disthy Putri (UIN Sunan Gunung Djati Bandung, 2023)
This research is entitled